Challenges for Young Engineers in the next Millenium - Sarwate, Dilip M. (Journal of Engineering Education Transformations, 2000)
Changing Economic Scenario: All of us are living in the times which are changing rapidly. The changes are affecting us individually as well as organisationally. We will have to understand these changes properly and will have to be proactive, the effect of changes are: • A passlve individual and organisation will soon face extinction • An adaptive individual and organisation will manage to survive • A creative individual and organisation will be able' to enjoy growth Let us study some of these changes.